Nosocomial Infection Control in the Children's and Maternity Hospital ''Harapan Kita''. Early Warning System - Aliamran Rasjid; H. A. M. Yusuf; Diwyo Soegondo; Leonard Napitupulu (Paediatrica Indonesiana, 1988)
In a children's and maternity hospital, where many high risk patients are hospitalized, a comprehensive but cheap surveillance system is of paramount importance for the improvement of hospital administration, formulation of hospital policy on antibiotic use and the nosocomial infection control programmes. The epidemiological data were primarily collected in a comprehensive built-in monitoring and surveillance programmes of this hospital, and had been distributed throughout the hospital periodically. The collected data had been broken down into (1) summary of ten leading infectious cases of hospitalized patient by tentative and final diagnosis; (2) types of culture by ward; (3) number of culture by sex and age group; (4) types of bacteria by ward; and (5) types of bacteria by culture. The classification of wards is indirectly inherent to the social- strata of the patients. For the refinement of information, they were broken down into data on bed-occupancy by ward, and data on hospitalized patients by sex and age groups as well.